Pengaruh Social Media Influencer dan Persepsi Kualitas Produk terhadap Minat Beli dengan Kepercayaan Merek sebagai Variabel Moderator - Adinda Dwi Ariyanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The rapid development of the cosmetics industry and the increase in social media users have encouraged companies to utilize influencers as a marketing strategy. This study aims to analyze social media influencer and product quality perceptions on the purchase intention of Hanasui product with brand trust as a moderator. This study uses a quantitative approach by conducting a questionnaire ti 146 respondents. The result show that social media influencer and product quality perceptions have a pocitif and significant effect on putchase intention. Bbrand trust was found to moderate the relationship between social media influencer and purchase intentions with a weak effect, while teh relationship between product quality perceptons and purchase intention didn’t show significant effect. The result empharuze the important of influencer stratef=gy management and strengthening brand trsut in increasing customer purchase intention.